The Involvement of Reviews in Online Travel Agencies to Increase Hotel Booking Intention in Batam - Putri, Desyanti; Sihombing, Dame Afrina; Hariyanto, Oda Ignatius Besar (Jurnal Manajemen Pelayanan Hotel, 2023)
Hotel reservations are currently dominated by online bookings from Online Travel Agent, therefore thisresearch was created to assist hoteliers in knowing how the role of online reviews can influence consumerpurchase intentions in making online reservations. There is no previous research that discusses this topic withthe setting in Batam, so this research was made to discuss it. This research used quantitative method and testedusing IBM SPSS, with the target population of respondents who have made hotel reservations using OTA inBatam, at the end of this study it is proven that the independent and mediating variables have a significantinfluence on the dependent variable. However, this study has limitations, which there are still invalid items andthere are still many that can be researched in more detail for further research.Keywords: Online Booking Intention, Purchase Intention, Reviewer Expertise, Online Travel Agent